2022
DOI: 10.3390/ma15103698
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flow Field Optimization of an Asymmetric Multi-Strand Tundish on the Quality Consistency of Cracking Con-Rod Steel

Abstract: Cracking con-rod is an advanced high-precision connecting structure based on brittle expansion, breaking and reconnection of steel, to solve the problem of assembly circle missing. High carbon micro-alloyed steel C70S6, as a dominant material for the production of cracking con-rod, has extremely strict requirements on non-metallic inclusions in steel and microstructure stability. Continuous casting tundish plays an important role in removing large-sized inclusions and stabilizing casting quality. Aiming at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Moreover, production trials have identified that the structures of multi-strand asymmetric tundishes and the instability of steel cleanliness during non-steady-state casting are major constraints in the production of high-quality steel. 22,23 Therefore, this study aims to optimise the structure of a super-large round bloom casting three-strand asymmetric tundish at a certain steel plant. By employing a combination of physical experiment and numerical simulation methods, the research enhances the flow field and temperature field distribution within the tundish.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, production trials have identified that the structures of multi-strand asymmetric tundishes and the instability of steel cleanliness during non-steady-state casting are major constraints in the production of high-quality steel. 22,23 Therefore, this study aims to optimise the structure of a super-large round bloom casting three-strand asymmetric tundish at a certain steel plant. By employing a combination of physical experiment and numerical simulation methods, the research enhances the flow field and temperature field distribution within the tundish.…”
Section: Introductionmentioning
confidence: 99%
“…To meet the demands of producing clean steel, researchers have employed both physical [1][2][3][4][5] and mathematical [6][7][8][9][10][11] simulation methods, focusing on the flow of molten steel. This entails optimizing flow control devices [12,13], adjusting process parameters [14,15], implementing gas blowing in the tundish [16,17], and utilizing induction heating technology [18,19]. These endeavors aim to continuously improve the tundish flow field [20,21], temperature distribution [22,23], and enhance inclusion removal efficiency [6,24,25], ultimately elevating the quality of steel products.…”
Section: Introductionmentioning
confidence: 99%
“…The worse the consistency, the greater the difference in casting quality between the strands. To reduce the inconsistent casting quality of C70S6 steel, Tie et al [ 21 ] optimized the tundish structure based on numerical simulations and industrial trials. After optimization, the difference in the columnar crystal ratio of the corresponding bloom casting decreased from 2.27%–3.17% to 1.26%–1.85%, and the consistency of the central carbon segregation index improved significantly.…”
Section: Introductionmentioning
confidence: 99%